Composite of Chitosan Vanilin / Sulfonated Polystyrene As Polymer Electrolyte Membranes: Cationic Exchange Capacity, Swelling Degree And Thermal Properties - Edi Pramono; Candra Purnawan; Yuniawan Hidayat; Jati Wulansari; Sayekti Wahyuningsih (ALCHEMY Jurnal Penelitian Kimia, 2014)
Research on the preparation and characterization of sulfonated polystyrene (PST) /chitosan vanillin (KV) composite as electrolyte membranes has been conducted in order to investigate the effect of PST and KV composition  to its chemical and physical properties. Polystyrene was modified by sulfonation reaction to produces PST, meanwhile chitosan was modified by schift base reaction to produces KV. The composite membranes were prepared by casting method and were characterized in order to identify the functional groups contained in the composite, the cation exchange capacity (CEC), the Swelling Degree (SD), the thermal properties and the morphology. The peak of imine vibration in the FTIR spectrum indicates that the chitosan vanilin was succesfully synthesized. Meanwhile, the peak of sulfonate vibration indicates the product of sulfonation on polystyrene. The result of CEC analysis shows that the addition of sulfonate groups on polystyrene and the addition of phenolic groups on chitosan increase the CEC value. The increasing of PST and KV concentration in membrane enhance the CEC value. However, the increasing of PST concentration in membrane composition even decrease the Swelling Degree of membranes. Meanwhile, the increasing of KV concentration increase the swelling degree of membranes. Thermal analysis shows that the thermal decomposition of membranes occurs in three stages i.e. the dehydration of water molecules, the degradation of the subtituen groups and the plasticizer and the degradation of the back bone of chitosan and polystyrene.